Unravelling the multi-scale structure of vertebrate scavenger communities: The role of beta-diversity in livestock carcass consumption - María Eugenia Cabrera-García; Patricia Mateo-Tomás; José Hernán Sarasola; Juan I. Zanón Martínez; Beatriz Martínez-Miranzo; Pedro P. Olea (Basic and Applied Ecology)
Understanding the structure of communities across multiple scales is useful for predicting impacts on biodiversity and ecosystem functioning. Scavenging, an important ecological function performed by scavenger assemblages, stands as a significant force shaping ecosystems. Using biodiversity partitioning, we assess the relative contribution of multiple scales (i.e., within and among individual carcasses, species and habitats) to the richness and Shannon diversity of vertebrate scavenger communities consuming anthropogenic food subsidies (i.e. livestock carrion) in central Argentina. We further evaluate the potential effect of carcass and habitat characteristics (including human impact) on the richness, abundance and diversity of vertebrate scavengers. A total of 31 carcasses, 22 of cow and nine of sheep, were monitored using remote cameras in cropland and natural habitats, recording consumption by 10 vertebrate species (four birds and six mammals). 50 % of scavenger species were observed at carcass level (α1 = 4.94 species), a contribution lower than expected by chance. While the turnover of species among carcasses (β1 diversity) significantly contributed (40 %) to regional richness (γ diversity), turnover of species between carrion types and habitats (β2 diversity) contributed a smaller fraction (10 %). Partitioning of Shannon diversity showed similar patterns to richness. Scavenger abundance increased during spring and was positively influenced by carcass weight; furthermore, carcasses in croplands supported less abundance that those located in natural habitats. Aligning with the theory of carrion unpredictability in maintaining biodiversity, our results suggest that scavenger species replacement (turnover) at human-mediated carcasses scattered in the field plays a significant role in shaping vertebrate scavenger assemblages.